Sexual size dimorphism and testis size allometry in tuco-tucos (Rodentia: Ctenomyidae) - Bidau, Claudio Juan (2013)
We studied sexual size dimorphism (SSD) and testes size allometry in 97 natural populations, including 39 nominal species and 19 unnamed or undescribed forms, of tuco-tucos ( Ctenomys ) from Argentina, Bolivia, Chile, Paraguay, and Uruguay in order to gain insight on the existence of sperm competition in these solitary, territorial, and possibly polygynic subterranean rodents. Our results indicated that sex-biased SSD occurs within the genus and also within lower taxa. SSD conforms to Rensch ’ s rule. Testes size showed a strong negative allo metry when compared with male body mass both across and within species, clearly suggesting the operation of sperm competition in this genus. Thus, within a Ctenomys population, small males would invest more than larger males in testes growth and thus in ejaculate quality, which would counterbalance their presumably lower chances of accessing females due to their smaller body size.